1979
DOI: 10.1001/archderm.115.7.884
|View full text |Cite
|
Sign up to set email alerts
|

Palmar-plantar lichen sclerosus et atrophicus

Abstract: A 57-year-old woman has had lichen sclerosus et atrophicus confined to the palms and soles for the past six years. Diagnosis was confirmed by histologic study. Our patient's disease has been resistant to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…In 1979, Petrozzi et al . 8 described a woman presenting with palmoplantar LS, similar to the case described here. Since that time, there have been only a few reports of exclusive acral involvement.…”
supporting
confidence: 73%
“…In 1979, Petrozzi et al . 8 described a woman presenting with palmoplantar LS, similar to the case described here. Since that time, there have been only a few reports of exclusive acral involvement.…”
supporting
confidence: 73%
“…The first reported patient with palmar involvement of LS&A was described by Purres and Krull 2 in 1971; their patient also had widespread cutaneous involvement and was resistant to treatment. In 1979, Petrozzi et al 4 reported a case of LS&A limited exclusively to the palms and soles that was resistant to salicylic acid and topical steroids. Tudino and Wong 3 in 1984 reported a female patient with extragenital LS&A with involvement of the palms and flexural wrists with hemorrhagic bullae.…”
Section: Discussionmentioning
confidence: 99%
“… 1 To our knowledge, we report the fifth case of extragenital LS&A with palmar involvement in the English-language literature. 2 , 3 , 4 , 5…”
Section: Introductionmentioning
confidence: 99%
“…Nous en avons trouvé cinq dans la littérature : deux touchant les faces palmoplantaires [10,11], sous forme de papules kératosiques déprimées des paumes, et de papules blanches lisses ou d'érythème desquamatif sur les plantes et trois atteignant les faces dorsales [12,13,9] sous forme de papules pâles scléreuses, ou de macules érythémateuses des replis sus-unguéaux des doigts, avec parfois une onychopathie [9,12] à type d'onychodystrophie ou d'ongles striés. Les lésions décrites paraîssent similaires à celles de la malade présentée, mais aucun de ces cinq cas ne touchait les pieds et les mains sur leurs deux faces, comme dans notre observation.…”
Section: Discussionunclassified